Current strategies for the long-term assessment, monitoring, and management of cystic fibrosis patients treated with CFTR modulator therapy - Elborn, J. Stuart; Mall, Marcus A. (Journal of cystic fibrosis, 2017)
The content for this activity is based on the satellite symposium, “Current Strategies for the Long-term Assessment, Monitoring, and Management for Cystic Fibrosis Patients Treated with CFTR Modulator Therapy” that was presented at the 39th European Cystic Fibrosis Society Conference on June 10, 2016 (Online access: http://courses.elseviercme.com/ecfs2016e/619e). The emergence of novel targeted agents, that directly correct CFTR loss function alleles, has created new treatment opportunities for patients with cystic fibrosis with advanced disease. Knowledge of the role of these agents in the clinical setting is quickly evolving and will require physicians to stay acquainted with the latest data as well as evidence-based treatment guidelines in order to achieve optimized cystic fibrosis patient care. Ideally, after diagnosis, a personalized approach would be adapted and tailored to the patient through genome-informed medicine. However, due to the relative recentness of genomic-based therapeutics, physicians may have a limited knowledge base regarding these new treatment options and how to best incorporate these agents into patient management plans. Although cystic fibrosis is still largely regarded as a pediatric disease, the median survival for patients is 35years of age. Consequently, pediatric-to-adult cystic fibrosis care programs would allow suitable preparation time for this transition and develop a standardized group of self-care and management skills.
Gesehen am 27.11.2018